A case of necrotizing fasciitis following intra-articular injections – Iatrogenic or spontaneous?. (February 2022) - Matsuki, Jumpei; Ishigami, Akiko; Tanaka, Motonari; Hata, Satoshi; Ishida, Yuko; Nosaka, Mizuho; Kuninaka, Yumi; Yamamoto, Hiroki; Shimada, Emi; Hashizume, Yumiko; Takayasu, Tatsunori; Kimura, Akihiko; et al.
Graphical abstract: Highlights: An elderly female passed away one day after intra-articular injection. An autopsy revealed necrotizing fasciitis only around injection sites. The cause of her death was diagnosed as streptococcal toxic shock syndrome. Inadequate procedures can cause post-injection severe streptococcal infection. Abstract: Here, we report a case of necrotizing fasciitis following intra-articular injection of hyaluronic acid. A 73-year-old female received intra-articular injections of hyaluronic acid due to arthralgia at the left shoulder and knee, and was found dead in her living room at one day. At the forensic autopsy, injection marks with bullae and erythema were found at the left shoulder and knee and liquefactive necrosis of muscle tissues was observed in the left but not right extremities. Histopathological examinations of the left upper arm and thigh revealed severe rhabdomyolysis with lots of bacterial clusters. Bacteriological examinations detected group A Streptococcus from intracardiac blood and affected muscle tissues. Postmortem biochemical analysis of blood showed escalated blood urea nitrogen (133.8 mg/dL), creatinine (4.57 mg/dL) and C-reactive protein (45.0 mg/dL). The cause of her death was diagnosed as streptococcal toxic shock syndrome (STSS). Moreover, it was suggested that the injection was inappropriately conducted and served as a portal of bacterial entry.